YOGIC MANAGEMENT FOR HYPOTHYROIDISM: A CASE STUDY (International Journal of Ayurveda and Pharma Research, 2018)
The thyroid is butterfly shaped gland, and the pituitary gland (another gland located in the brain) regulates it. Hypothyroidism (underactive thyroid) refers to any state in which a person's thyroid hormone production is below normal. In Modern medicine Standard treatment for hypothyroidism involves daily use of the synthetic thyroid hormone levothyroxine (Levothroid, Synthroid, others). A patient might become dependent on these drugs for life.. We present a case where a patient was suffering from hypothyroidism for the last 6 months and got positive results by integrated approach with yoga therapy. The Patient was suffering for hypothyroidism with TSH level of 36.6. After the end of the yoga therapy the TSH level was reduced to 5.82.The patient did not undergo treatment with modern medicine.